Mechanistic Insights and Anti-cancer Activity of 2H-benzo[b][1,4]oxazin-3(4H)-one Linked 1,2,3-Triazoles in Human Cancer Cells - Liu, Qingying; Hou, Xixi; Tian, Mingyue; He, Baoyu; Guo, Jingjing; Guo, Yajie; Yang, Jianxue (Frontiers in Pharmacology, 2025)
A series of 2H-benzo[b][1,4] oxazin-3(4H)-one derivatives linked to 1,2,3-triazoles were designed, synthesized, and evaluated for their anticancer activity in several human cancer cell lines, including A549 (lung), Huh7 (liver), MCF-7 (breast), HCT-116 (colon), and SKOV3 (ovary). Cell viability assays revealed that these compounds exhibited the most potent activity against A549 cells. Among them, compounds 14b and 14c demonstrated the strongest inhibitory effects, with IC50 values of 7.59 ± 0.31 μM and 18.52 ± 0.59 μM, respectively. Flow cytometry analysis further confirmed that compounds 14b and 14c induced significant apoptosis. Additional studies showed that these compounds elevated reactive oxygen species (ROS) levels, which may contribute to apoptosis. Moreover, compounds 14b and 14c notably increased the number of dead cells while reducing viable cell counts. Western blot analysis indicated that these compounds could induce DNA damage and autophagy, which may play a key role in their anticancer effects.